The Impact of Plastic Waste on Health and Free Health Checks For The Community of Lopo Village, Gorontalo Regency - Siti Surya Indah Nurdin; Zul Fikar Ahmad; Paramita S Bani; Putri Waruis Buhang (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Plastic is involved in every activity of human life. Plastic waste has caused health problems. One of the efforts to reduce the health impact caused by plastic on humans is to conduct health education. This service aims to provide education to the Lopo village community regarding the impact of plastic waste and conduct health checks on village communities. The service will be held in September 2021 in Lopo Village, Batudaa District, Gorontalo Regency. The service is carried out in the form of counseling using the lecture method with the help of Power Point which is then discussed with the participants. The participants of the activity are all the people of Lopo Village. The implementation of activities is self-funded by the executor. Service activities have been carried out well.